Discovery of bicyclic pyrazoles as class III histone deacetylase SIRT1 and SIRT2 inhibitors. Issue 12 (15th June 2015) - Therrien, Eric; Larouche, Guillaume; Nguyen, Natalie; Rahil, Jubrail; Lemieux, Anne-Marie; Li, Zuomei; Fournel, Marielle; Yan, Theresa P.; Landry, Anne-Julie; Lefebvre, Sylvain; Wang, James J.; MacBeth, Kyle; et al.
Graphical abstract: Abstract: A series of bicyclic pyrazole carboxamides was synthesized and tested for inhibitory activity against the class III deacetylase sirtuin enzymes. Moderate to low micromolar inhibitory activities were obtained against SIRT1 and SIRT2. These bicyclic pyrazole compounds represent a new class of sirtuin inhibitors with a preference for SIRT1 over SIRT2.